Aloe-Emodin Derivative, an Anthraquinone Compound, Attenuates Pyroptosis by Targeting NLRP3 Inflammasome in Diabetic Cardiomyopathy - Yingying Hu; Shuqian Zhang; Han Lou; Monayo Seth Mikaye; Run Xu; Ziyu Meng; Menghan Du; Pingping Tang; Zhouxiu Chen; Yongchao Chen; Xin Liu; Zhimin Du; et al. (MDPI AG, 2023)
Diabetic cardiomyopathy (DCM) is widely recognized as a major contributing factor to the development of heart failure in patients with diabetes. Previous studies have demonstrated the potential benefits of traditional herbal medicine for alleviating the symptoms of cardiomyopathy. We have chemically designed and synthesized a novel compound called aloe-emodin derivative (AED), which belongs to the aloe-emodin (AE) family of compounds. AED was formed by covalent binding of monomethyl succinate to the anthraquinone mother nucleus of AE using chemical synthesis techniques. The purpose of this study was to investigate the effects and mechanisms of AED in treating DCM. We induced type 2 diabetes in Sprague-Dawley (SD) rats by administering a high-fat diet and streptozotocin (STZ) injections. The rats were randomly divided into six groups: control, DCM, AED low concentration (50 mg/kg/day), AED high concentration (100 mg/kg/day), AE (100 mg/kg/day), and positive control (glyburide, 2 mg/kg/day) groups. There were eight rats in each group. The rats that attained fasting blood glucose of ˃16.7 mmol/L were considered successful models. We observed significant improvements in cardiac function in the DCM rats with both AED and AE following four weeks of intragastric treatment. However, AED had a more pronounced therapeutic effect on DCM compared to AE. AED exhibited an inhibitory effect on the inflammatory response in the hearts of DCM rats and high-glucose-treated H9C2 cells by suppressing the pyroptosis pathway mediated by the nucleotide-binding oligomerization domain (NOD)-like receptor pyrin domain 3 (NLRP3) inflammasome. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of differentially expressed genes showed a significant enrichment in the NOD-like receptor signaling pathway compared to the high-glucose group. Furthermore, overexpression of NLRP3 effectively reversed the anti-pyroptosis effects of AED in high-glucose-treated H9C2 cells. This study is the first to demonstrate that AED possesses the ability to inhibit myocardial pyroptosis in DCM. Targeting the pyroptosis pathway mediated by the NLRP3 inflammasome could provide a promising therapeutic strategy to enhance our understanding and treatment of DCM.